The Predictive Factors of Acne Scarring and Post-Inflammatory Hyperpigmentation: A Retrospective Cohort Study - Alamri A; Alzahrani D; Alharbi G; Jan R; Alsubaie LA; Alghamdi A; Abualola AH; Jfri A (Clinical, Cosmetic and Investigational Dermatology)
Awadh Alamri,1– 3 Dhaii Alzahrani,1,2 Ghadi Alharbi,1,2 Rami Jan,1,2 Lulu Abdullah Alsubaie,1,2 Amjad Alghamdi,1,2 Amal H Abualola,1,2 Abdulhadi Jfri1– 3 1College of Medicine, King Saud Bin Abdulaziz University for Health Sciences, Jeddah, Saudi Arabia; 2King Abdullah International Medical Research Center, Jeddah, Saudi Arabia; 3Department of Dermatology, King Abdulaziz Medical City, Jeddah, Saudi ArabiaCorrespondence: Rami Jan, College of Medicine – Jeddah, King Saud bin Abdulaziz University for Health Sciences, P.O.Box.9515, Jeddah, 21423, Saudi Arabia, Email ramiqj@gmail.comIntroduction: Acne vulgaris, a prevalent dermatological condition, often results in long-term complications such as scarring and hyperpigmentation. While extensive research has focused on treatment modalities, there is a notable gap in understanding the factors contributing to the development of acne scarring and post-inflammatory hyperpigmentation (PIH).Purpose: This study was conducted to identify the factors contributing to the development of acne scarring and post-inflammatory hyperpigmentation (PIH).Patients and Methods: This retrospective cohort study, conducted at King Abdulaziz Medical City, Jeddah, Saudi Arabia, analyzed data from patients with acne vulgaris between 2016 and 2023 using the hospital’s health information system, BESTCare. Statistical analysis was performed using RStudio (R version 4.3.1). We constructed a multivariable, multinomial logistic regression model to assess the independent predictors of four acne complication groups; no scarring/PIH, scarring alone, PIH alone, and acne scarring with PIH.Results: Among 417 analyzed participants, 95 participants had acne scarring (22.8%), 93 participants had PIH alone (22.3%), and 151 participants had both acne scarring with PIH (36.2%), and only 78 participants did not develop scarring or PIH (18.7%). Isotretinoin use and papules acne were associated with increased risk of acne complications. While adapalene gel was protective against acne scarring only.Conclusion: This retrospective study sheds light on factors influencing acne scarring and PIH among Acne Vulgaris patients. Our findings provide valuable insights for tailoring interventions and advancing our understanding of acne vulgaris complications in the future.Keywords: acne vulgaris, acne scarring, post-inflammatory hyperpigmentation, predictive factors, retrospective cohort study